2021
DOI: 10.1002/qute.202000103
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Mode Correction of Single Photons Using Machine Learning

Abstract: Spatial modes of light constitute valuable resources for a variety of quantum technologies ranging from quantum communication and quantum imaging to remote sensing. Nevertheless, their vulnerabilities to phase distortions, induced by random media, impose significant limitations on the realistic implementation of numerous quantum‐photonic technologies. Unfortunately, this problem is exacerbated at the single‐photon level. Over the last two decades, this challenging problem has been tackled through conventional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…Machine learning and neural-networks-based algorithms have been recently used, among other things, to classify structured light [91,105,123] and for noise compensation [94][95][96][97][98][99][100][101][102]124]. CNNs are a class of neural-network architectures especially suited to process images for classification and regression tasks.…”
Section: Machine-learning-based Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning and neural-networks-based algorithms have been recently used, among other things, to classify structured light [91,105,123] and for noise compensation [94][95][96][97][98][99][100][101][102]124]. CNNs are a class of neural-network architectures especially suited to process images for classification and regression tasks.…”
Section: Machine-learning-based Classificationmentioning
confidence: 99%
“…Machine learning (ML) methods have also recently proved valuable in the context of the reconstruction of the properties of structured light. In particular, supervised and unsupervised learning techniques were used to classify OAM states propagating through free-space [91][92][93] and through turbulent environments [94][95][96][97][98][99][100][101][102][103][104], as well as to classify and reconstruct VVB states [105,106].…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the network consists of a group of interconnected neurons arranged in layers. Here, the information flows only in one direction, from input to output [37,38]. As indicated in Fig.…”
mentioning
confidence: 99%
“…Additionally, it has been shown that high-dimensional Hilbert spaces defined in the OAM basis can increase the robustness of secure protocols for quantum communication [13][14][15]. However, despite the enormous potential of structured photons, their vulnerabilities to phase distortions impose important limitations on the realistic implementation of quantum technologies [3,5,6,13,[16][17][18][19][20]. Indeed, LG beams are not eigenmodes of commercial optical fibers and consequently their spatial profile is not preserved upon propagation.…”
mentioning
confidence: 99%
“…In the field of photonics, there has been extensive research devoted to developing artificial neural networks for the implementation of novel optical instruments [33][34][35]. Indeed, convolutional neural networks (CNNs) have enabled the demonstration of new imaging schemes working at the single-photon level [17,36,37]. These protocols have been employed to characterize structured photons in the Laguerre-Gaussian (LG), Hermite-Gaussian (HG), and Bessel-Gaussian (BG) bases [3,5,6,[36][37][38][39][40][41].…”
mentioning
confidence: 99%